Scintillation Properties of Pr-Doped Lanthanum Pyrosilicate Single Crystals - Prom Kantuptim; Takumi Kato; Daisuke Nakauchi; Noriaki Kawaguchi; Takayuki Yanagida (Crystals, 2022)
Five samples of lanthanum pyrosilicate (La2Si2O7) single crystals with 0.5–10.0% Praseodymium (Pr)-doping concentrations were synthesized by the floating-zone method. Photoluminescence and scintillation properties of these crystals were investigated in this study for the first time. The multiple emissions from electron transitions of Pr3+ were observed on both a photoluminescence emission map and scintillation spectra, including the desired emission band of Pr3+ 5d–4f transition at 250–310 nm. The major photoluminescence and scintillation decay times were approximately 19 and 26 ns, respectively. When compared with commercial scintillators such as Tl-doped cesium iodide (CsI), the Pr-doped La2Si2O7 samples presented a respectively low afterglow level of 32 ppm after 20 ms of X-ray irradiation. Under 662 keV γ-ray irradiation from 137Cs, the 3.0% Pr-doped La2Si2O7 sample presented a scintillation light yield of 3200 ph/MeV, which was the best value among the tested samples.